2021
DOI: 10.1051/0004-6361/202140559
|View full text |Cite
|
Sign up to set email alerts
|

The GAPS Programme at TNG

Abstract: Context. Giant planets in short-period orbits around bright stars represent optimal candidates for atmospheric and dynamical studies of exoplanetary systems. Aims. We aim to analyse four transits of WASP-33b observed with the optical high-resolution HARPS-N spectrograph to confirm its nodal precession, study its atmosphere, and investigate the presence of star-planet interactions. Methods. We extracted the mean line profiles of the spectra using the least-squares deconvolution method, and we analysed the Doppl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 86 publications
7
31
2
Order By: Relevance
“…One of the goals of this study was to improve upon the established results for the orbital parameters of WASP-33 b and KELT-9 b by previous works (e.g., Johnson et al 2015;Gaudi et al 2017;Watanabe et al 2020), given the longer baseline for observations and making use of the measured nodal precession of the planets' orbits. As such, we confirm for WASP-33 b that i * is close to 90 deg, and determine a best-fit value for J 2 significantly lower compared to previous works with shorter baselines (e.g., Watanabe et al 2020), and consistent with recent work with similar extended baseline coverage (Borsa et al 2021) (see also Table 3).…”
Section: Improvements On Previous Results and New Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…One of the goals of this study was to improve upon the established results for the orbital parameters of WASP-33 b and KELT-9 b by previous works (e.g., Johnson et al 2015;Gaudi et al 2017;Watanabe et al 2020), given the longer baseline for observations and making use of the measured nodal precession of the planets' orbits. As such, we confirm for WASP-33 b that i * is close to 90 deg, and determine a best-fit value for J 2 significantly lower compared to previous works with shorter baselines (e.g., Watanabe et al 2020), and consistent with recent work with similar extended baseline coverage (Borsa et al 2021) (see also Table 3).…”
Section: Improvements On Previous Results and New Findingssupporting
confidence: 90%
“…We model the observed changes of the projected obliquity λ and impact parameter b over time, assuming pre-cession of the nodes due to tidal interactions between the planets and their host stars. Our analysis is similar to that discussed in previous works (e.g., Watanabe et al 2020;Borsa et al 2021). We translate the observed values of λ and b into values for the ascending node versus the line-of-sight, Ω, and the inclination of the planetary orbital plane versus the plane of the sky, I, via the equations tan Ω = − sin λ tan i p…”
Section: Modeling Planetary Precessionmentioning
confidence: 80%
See 2 more Smart Citations
“…The planetary companion of WASP-33 is a hot Jupiter (P ∼ 1.219867 ± 4.2 • 10 −5 days (von Essen et al 2020), M P ∼ 2.10 ± 0.14M J , R P ∼ 1.59 ± 0.07R J (Chakrabarty & Sengupta 2019)). WASP-33b (Christian et al 2006) was the first confirmed planet orbiting a δ Sct host star (Herrero et al 2011), and it has been analyzed thoroughly including Doppler tomography and radial velocity measurements (Collier Cameron et al 2010;Watanabe et al 2020;Borsa et al 2021) as well as ground-based photometry (von Essen et al 2014). Using the TESS light curve, von Essen et al (2020) improved the precision of the known transit parameters.…”
Section: Introductionmentioning
confidence: 99%